Activated Neutrophils Are Associated with Pediatric Cerebral Malaria Vasculopathy in Malawian Children - Catherine Manix Feintuch (American Society for Microbiology, 2016)
ABSTRACT Most patients with cerebral malaria (CM) sustain cerebral microvascular sequestration of Plasmodium falciparum-infected red blood cells (iRBCs). Although many young children are infected with P. falciparum, CM remains a rare outcome; thus, we hypothesized that specific host conditions facilitate iRBC cerebral sequestration. To identify these host factors, we compared the peripheral whole-blood transcriptomes of Malawian children with iRBC cerebral sequestration, identified as malarial-retinopathy-positive CM (Ret+CM), to the transcriptomes of children with CM and no cerebral iRBC sequestration, defined as malarial-retinopathy-negative CM (Ret-CM). Ret+CM was associated with upregulation of 103 gene set pathways, including cytokine, blood coagulation, and extracellular matrix (ECM) pathways (P < 0.01; false-discovery rate [FDR] of <0.05). Neutrophil transcripts were the most highly upregulated individual transcripts in Ret+CM patients. Activated neutrophils can modulate diverse host processes, including the ECM, inflammation, and platelet biology to potentially facilitate parasite sequestration. Therefore, we compared plasma neutrophil proteins and neutrophil chemotaxis between Ret+CM and Ret-CM patients. Plasma levels of human neutrophil elastase, myeloperoxidase, and proteinase 3, but not lactoferrin or lipocalin, were elevated in Ret+CM patients, and neutrophil chemotaxis was impaired, possibly related to increased plasma heme. Neutrophils were rarely seen in CM brain microvasculature autopsy samples, and no neutrophil extracellular traps were found, suggesting that a putative neutrophil effect on endothelial cell biology results from neutrophil soluble factors rather than direct neutrophil cellular tissue effects. Meanwhile, children with Ret-CM had lower levels of inflammation, higher levels of alpha interferon, and upregulation of Toll-like receptor pathways and other host transcriptional pathways, which may represent responses that do not favor cerebral iRBC sequestration. IMPORTANCE There were approximately 198 million cases of malaria worldwide in 2013, with an estimated 584,000 deaths occurring mostly in sub-Saharan African children. CM is a severe and rare form of Plasmodium falciparum infection and is associated with high rates of mortality and neurological morbidity, despite antimalarial treatment. A greater understanding of the pathophysiology of CM would allow the development of adjunctive therapies to improve clinical outcomes. A hallmark of CM is cerebral microvasculature sequestration of P. falciparum-infected red blood cells (iRBCs), which results in vasculopathy in some patients. Our data provide a global analysis of the host pathways associated with CM and newly identify an association of activated neutrophils with brain iRBC sequestration. Products of activated neutrophils could alter endothelial cell receptors and coagulation to facilitate iRBC adherence. Future studies can now examine the role of neutrophils in CM pathogenesis to improve health outcomes.